Evaluation of community-based mental health programme in selected districts of Nepal 2015. (2015)
SUMMARY: Context of the evaluation: With the aid of the World Health Organization (WHO), Country Office for Nepal, a community-based mental health programme incorporating two components; mental health outreach camp and training of community health workers was commenced by the Mental Hospital in December, 2010 for a year. However, the programme with the goal of increasing accessibility of mental health services is still underway in Dhading and Nuwakot with own resources of the Mental Hospital. As the programme crosses its four years; necessity of evaluation does exist in order to have an insight into current status, achievement of objectives, and justify the significance of its presence to the relevant stakeholders. Therefore, evaluation was carried out independently by the Nepal Health Research Council (NHRC) to help to make a decision on the amendment and expansion of the programme; giving the figure of relevance, efficiency, effectiveness, sustainability, and impact. Methodology: Both qualitative and quantitative methods were employed. Study participants were Public Health Inspectors, trained health workers, including female community health volunteers (FCHVs), community leaders actively involved in the outreach camp, and clients of outreach camp. Qualitative information was assembled through key informant interview (KII) guideline and exit client interview guideline. Checklist was used for quantitative data. Quantitative information were cleaned, entered, and analyzed in the Statistical Package for Social Science full version 16.0. Thematic analysis was the process used for accumulated qualitative data. The study stood by ethical guidelines, with an ethical approval from an independent Ethical Review Board of NHRC and a written informed consent from the participants. Relevance of the programme: Demonstrating the scenarios of mental health problem burden, justified programme objectives in relation to beneficiaries need, competency building of community health workers, overwhelming response of clients, adequate in addition to acceptable services, sufficient and competent mental health teams to manage most of cases excluding severe cases; programme was considerably relevant in the duo districts. Nonetheless, what left unconcerned in both the sites was prioritization of mental health by district health authorities. Dearth of equitable services somehow questioned the programme's significance. Efficiency of the programme: Provided the unavailability of the cost of every single unit of the programme, efficiency could not be appraised well. Nevertheless, with raw information of NRs. 1.5 million as an input, and a number of local health workers trained along with number of mentally ill treated under the same input, could be considered a sort of efficiency; though this component needs further investigation. Effectiveness of the programme: In some measures, the programme remained effective. It was particularly due to limited institutionalization of mental health in district health system, satisfactory numbers of clients mostly from camp adjacent areas, partly accessible mental health services, content of clients with services, reported increment in counseling and referral of clients by community health workers, and concentrated awareness among mental ill and their family. At both the locations, hindrances in the course of programmes effectiveness were: confined monitoring and supervision of the camp, no follow ups of trained community health worker's, restricted dissemination of camp's information up to the grass root level, infrequent involvement of district health authorities in the camp, and limited mental health capacity building endeavors by the District Health Office and other organizations. Fair to say, effectiveness was higher in Dhading district than its counterpart Nuwakot by certain degree. Unveiled supporting evidences were: active involvement of local non-governmental organization, Koshish providing fund of NRs. 15,000 per month to buy mental drugs for the camp, generation of community organization promoting mental health in the community, and active involvement of trained health workers in mental health promoting programmes. Sustainability of the programme: For both the districts, measuring in terms of continuation of outreach camp without external assistance, the programme looked sustainable in some way. Prospects of further continuation may be viewed in the context of number of organizations operating in Nuwakot and Dhading after the Gorkha Earthquake of 25 April 2015. A plenty of opportunities for collaborating with these organizations are therefore visible. Some piece of information showing the evidence of durability of results attributed to programme was noticed in Dhading. Explored events were: energetic involvement of local organization named Mental Swabalamban Group and community health workers, over the time in promoting community mental health. Impact of the programme: In light of the programme's running status, questions of the major impact of programme, sustainable change in the health of the population and marked results after the completion of programme could not be answered. Though, unintended short-term effect, discontinuation of drug use by some of the regular clients was noted due to shifting of Rajmarga Hospital's outreach camp to District Hospital in Dhading after the Gorkha Earthquake 2015. As the price of drugs surged after this event, most of the deprived people could not make it to afford increasing the pattern of drug use discontinuation. Lessons learned: Just an implementation of programme in isolation may not always work. Importance of supervision, monitoring, and evaluation also counts. All above that, factors influencing implementation, failure, and success of programme need to be considered equally; this was hardly found in this programme. Inadequate awareness of mental health in the community, still persisting negative perception of the community towards mental health problems, difficulty in counseling client and their family to refer to camp somehow hindered the success of the programme. Some of the beneficiary's vital needs crucially lacking were camp's wide coverage and frequency, thus affecting patient flow more or less. A great lack of coordination and collaboration with district health authorities and other private organizations greatly got into the way of promoting activities of outreach camp. It was also inadequate dissemination of message of outreach camp up to the grass root level that negatively impacted the programme's success. Paying attention to all these influences together with the socio-cultural environment, a refined programme incorporating these aspects may assist in reaching the goal of the programme. Recommendation: Owing to programme's relevance, mild effectiveness, and possible sustainability, community-based mental health programme deserves continuation, with the amendment in programme modality. Learning from strengths, weaknesses, opportunity and challenges of this programme, possible constructive approaches could be: focused monitoring and supervision of camp activities, training of all FCHVs, health worker's(HWs) of problem severe areas, orientation to mother groups(MGs) and key community persons of problem loaded areas, coordination and collaboration with private organizations with a lead of district health authorities, and active dissemination of message of outreach camp mobilizing community people. The current programme may be scaled up in other districts too; programme modality being harmonized with local circumstances and loads of mental cases.